Pengaruh Lama Waktu Fermentasi Terhadap Kandungan Kombucha Daun Kecapi (Sandoricum koetjape): The Effect of Fermentation Time on The Content of Kombucha From Sentul Leaves (Sandoricum koetjape) - Sarmila; Fajri Romadhan, Muhammad (Journal of Food Engineering, 2025)
Kombucha was a fermented beverage that contained various metabolite compounds beneficial to health. The content of these compounds was influenced by the duration of fermentation and the type of raw materials used. Sentul leaves (Sandoricum koetjape) had the potential to be used as a raw material for kombucha because they were rich in metabolite compounds. This study aimed to determine the effect of fermentation duration on the content of sentul leaf kombucha. The sentul leaf kombucha was fermented for 6, 7, 8, 9, and 10 days. The analyzed parameters included total phenol, pH, vitamin C, alcohol content, and organoleptic tests such as hedonic and quality score tests. Sentul leaf kombucha fermented for 7 days produced a total phenol content of 66.19 mg GAE/g, vitamin C content of 0.25 g/100 ml, a pH value of 3.43, and an alcohol content of 0.03013%. The organoleptic test with 35 untrained panelists showed that the 7-day fermented kombucha was moderately liked, with a brown color and a slightly sour aroma. The results of this study showed that the duration of fermentation affected the content of sentul leaf kombucha, with 7 days being the best fermentation time.